PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. BANK BCA KCP CITRA TOWERS KEMAYORAN - Nurman Ibrahim; Eddy Sanusi Silitonga (Jurnal Manajemen Bisnis Krisnadwipayana, 2021)
To determine the effect of work discipline and work environment on employee performance PT. Bank BCA KCP Citra Towers Kemayoran. This research is included in the category of causal associative research using a quantitative approach. The population in this study were all employees of PT. Bank BCA KCP Citra Towers Kemayoran, amounting to 30 people. The sample uses a saturated sampling technique, all members of the population are sampled, because the relative number is small, while the data analysis method uses partially and simultaneous linear regression. The results showed that partially or simultaneous work discipline and work environment had a positive and significant effect on the performance of the employees of PT. Bank BCA KCP Citra Towers Kemayoran.